STATUS QABDH (PENGUASAAN) DALAM TRANSAKSI TABUNGAN EMAS DIGITAL DI BANK SYARIAH INDONESIA: STUDI ATAS KONSEP QABDH HUKMI DALAM FIKIH MUAMALAH - Panji Lukito; Sisiliya Putri Febriyanti; Malvin Dianda (JSE: Jurnal Sharia Economica, 2026)
This research is in the field of Islamic economic law, specifically muamalah jurisprudence, focusing on the concept of qabdh (control) in digital gold savings transactions at Bank Syariah Indonesia. The purpose of this article is to analyze the conformity of digital gold savings practices with the concept of qabdh hukmi and assess its legal implications for the validity of transactions. This topic is important because the development of Islamic financial technology has resulted in a shift in the form of control from physical to digital, which requires fiqh legitimacy. The research method used is qualitative with a normative-empirical approach through literature studies and analysis of operational practices. The hypothesis of this research is that qabdh hukmi can be the basis for legitimizing digital gold transactions as long as they comply with sharia principles. The results show that the practice of digital gold savings at Bank Syariah Indonesia has fulfilled the elements of qabdh hukmi through recording ownership and customer access control. This research contributes to the development of contemporary ijtihad regarding the digitalization of Islamic assets. In conclusion, qabdh hukmi is relevant as a legal basis, thereby strengthening the validity of digital gold transactions in the modern Islamic banking system